ANALYSIS OF THE POTENTIAL ATTRACTION OF ECO-KARST TOURISM OF MARON RIVER, DERSONO VILLAGE, PRINGKUKU DISTRICT PACITAN REGENCY - Pipit Wijayanti; Muhammad Zaki Zamani (Universitas Sebelas Maret (UNS), 2022)
Tourism is one of the ways for residents at the village to gain income and aslo a contributor to the national economy. The tourism that is found in every village nowadays favors the potential of the surrounding nature. Pacitan Regency is known to have tourism potential related to the advantages of its karst landscape. Pacitan also got the nickname